Effects of multimedia integrated fine arts education on students' learning attitude and learning satisfaction - Sun, Xiaodong; Fu, Rong; Zhang, Guoqing; Chen, Chenin (Frontiers in Psychology, 2022)
The educational reform of the twenty-first century was a successful attempt in which high technology, media, and multimedia computer information work together. The use of instructional media doubled the effect with half the effort in promoting learners' motivation to learn. This was achieved by providing specific and authentic information, changing attitudes, and even being independent of instruction. The rapid development of technology also brings innovations in teaching media. The purpose of this study is to investigate the effects of multimedia integrated fine arts education on students. A quasi-experimental design was adopted in this study. College students from Shanxi Province were selected as the participants of a one-semester experimental study. The research results show significantly positive effects of (1) multimedia integrated fine arts education on learning attitude, (2) multimedia integrated fine arts education on learning satisfaction, and (3). mobile learning on learning satisfaction. The experimental observation revealed that, when fine arts works are exhibited through multimedia, students have closer contact with them. Students gradually feel more involved in art and show interest in art, as well as a desire to explore. Such a process of change will enable students to change their learning attitude into active absorption of professional knowledge of fine arts. As a result, their competence in fine arts can be improved significantly. It is expected that the results will contribute to the fine arts and humanities with practically tested theories as a reference for teachers and future studies in the field.